2017
DOI: 10.1177/0954411917692010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiological modelling of tendons: Review and future opportunities

Abstract: Tendons are adapted to carry large, repeated loads and are clinically important for the maintenance of musculoskeletal health in an increasing, actively ageing population, as well as in elite athletes. Tendons are known to adapt to mechanical loading. Also, their healing and disease processes are highly sensitive to mechanical load. Computational modelling approaches developed to capture this mechanobiological adaptation in tendons and other tissues have successfully addressed many important scientific and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 112 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…How mechanically activated downstream pathways potentially flip the balance between functional remodeling and fibrotic scarring will undoubtedly result in more targeted treatment of tendon disorders. For details on the pathways implicated in tendon mechanotransduction see [17,116,[271][272][273][274]. [57], thus potentially playing a role in age-related tendon disorders.…”
Section: Focal Adhesion-mediated Mechanical Signal Transductionmentioning
confidence: 99%
“…How mechanically activated downstream pathways potentially flip the balance between functional remodeling and fibrotic scarring will undoubtedly result in more targeted treatment of tendon disorders. For details on the pathways implicated in tendon mechanotransduction see [17,116,[271][272][273][274]. [57], thus potentially playing a role in age-related tendon disorders.…”
Section: Focal Adhesion-mediated Mechanical Signal Transductionmentioning
confidence: 99%
“…However, the precise magnitude, frequency, and duration of stimulation required for normal tendon homeostasis remain unknown. In addition, despite numerous in vivo, in vitro, and ex vivo studies on tendon mechanical properties and the development of prediction models (Galloway et al, 2013;Fang and Lake, 2016;Herod et al, 2016;Thorpe and Screen, 2016;Thompson et al, 2017;Chen et al, 2018;Carniel and Fancello, 2019;Theodossiou and Schiele, 2019), the precise in vivo loading levels required to induce tendon repair are yet unspecified. In this regard, further understanding of the in vivo loading of tendons is vital to understand the mechanobiological stimuli required to induce anabolic or reduce catabolic activity (Lavagnino et al, 2015).…”
Section: Tendonmentioning
confidence: 99%
“…This region is also the point at which the tangent modulus reaches its maximum value. Studies have found that over 4% strain can cause microscopic damage during the sliding of collagen fibrils ( Thompson et al, 2017 ). The failure region of the stress-strain curve demonstrates macroscopic tears associated with strain values over 8–10% ( Butler et al, 2000 ; Thompson et al, 2017 ).…”
Section: Structure and Biomechanics Of Tendonmentioning
confidence: 99%